1995
DOI: 10.1093/clinids/21.5.1220
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Severity of Invasive Group A Streptococcal Disease in Australia: Clinical and Molecular Epidemiological Features and Identification of a New Virulent M-Nontypeable Clone

Abstract: We conducted a 12-year review of all cases of group A streptococcal (GAS) bacteremia that were seen at Royal Children's Hospital in Melbourne, Australia, from 1982 through 1993. Forty-two cases were identified. There was a trend towards increased incidence of infections, as well as a clear increase in their severity, during the study period; more previously healthy children were affected during the last 6 years of the study (80% of cases) than during the first 6 years (47% of cases), and more complications occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
2
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 38 publications
5
64
2
4
Order By: Relevance
“…It is now clear from our analysis that a complex multistep (9). Moreover, it has been well documented (2,3,5,7,8,11,12,14,19) that epidemic M1 infections occurred in Norway, Sweden, Finland, Denmark, Australia, and Canada in the ensuing years. The result of the genetic events we describe here was an explosive intercontinental epidemic of serotype M1 human infections including pharyngitis and severe invasive diseases such as necrotizing fasciitis, the "flesh-eating" infection.…”
Section: Concluding Commentmentioning
confidence: 70%
See 3 more Smart Citations
“…It is now clear from our analysis that a complex multistep (9). Moreover, it has been well documented (2,3,5,7,8,11,12,14,19) that epidemic M1 infections occurred in Norway, Sweden, Finland, Denmark, Australia, and Canada in the ensuing years. The result of the genetic events we describe here was an explosive intercontinental epidemic of serotype M1 human infections including pharyngitis and severe invasive diseases such as necrotizing fasciitis, the "flesh-eating" infection.…”
Section: Concluding Commentmentioning
confidence: 70%
“…The result of the genetic events we describe here was an explosive intercontinental epidemic of serotype M1 human infections including pharyngitis and severe invasive diseases such as necrotizing fasciitis, the "flesh-eating" infection. GAS causes >600 million cases of human infections yearly, and extensive epidemiologic studies have shown that serotype M1 organisms are frequently the most abundant M protein serotype (3,4,7,9,14,(74)(75)(76). In conclusion, the molecular evolutionary events transpiring in just one bacterial cell ultimately produced many millions of human infections worldwide.…”
Section: Concluding Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the mid-1980s, a conspicuous increase in the incidence of invasive infections caused by group A streptococci (GAS) has been observed worldwide (3,9,10,18,27,37,38,53,70). Invasive GAS diseases include various clinical syndromes such as bacteremia, arthritis, pneumonia, puerperal sepsis, meningitis, and necrotizing fasciitis.…”
mentioning
confidence: 99%